PERAN PEMERINTAH DAERAH DALAM PENGELOLAAN SAMPAH BERKELANJUTAN: : ANALISIS KEBIJAKAN DAN IMPLEMENTASI HUKUM LINGKUNGAN MELALUI DATA DATA SISTEM INFORMASI PENGELOLAAN SAMPAH NASIONAL (SIPSN) PROVINSI JAWA BARAT - Rahma Idha Fitri; Irfan Setiawan (Institut Pemerintahan Dalam Negeri, 2025)
Waste is the residue of daily human activities and/or natural processes in solid form. Waste can be a burden and can also be a resource that needs to be processed to support environmental waste management. This study aims to analyze the role of local governments in sustainable waste management by evaluating the alignment of regional policies, the effectiveness of legal implementation, and institutional strengthening strategies and multi-stakeholder collaboration. The method used is qualitative descriptive-analytical with a case study approach in several regions, supplemented by document analysis (Regional Regulation, RPJMD, Law No. 18/2008 and No. 32/2009) and SIPSN data for 2024. The results of the study indicate that although regional policies such as Regional Regulation No. 12/2010 in West Java have adopted sustainable principles (3R, producer responsibility), their implementation still faces obstacles such as lack of regulatory harmonization, limited institutional capacity, and low public awareness. Strategic recommendations include strengthening recycling infrastructure, increasing multi-stakeholder collaboration, and locally-based education to achieve sustainable waste management.